Improvements in Out-of-Hospital Cardiac Arrest Survival from 1998 to 2013. (3rd September 2017) - Yamaguchi, Yutaka; Woodin, Jeff A.; Gibo, Koichiro; Zive, Dana M.; Daya, Mohamud R.
Abstract: Objectives : Out-of-hospital cardiac arrest (OHCA) remains a major public health burden. Aggregate OHCA survival to hospital discharge has reportedly remained unchanged at 7.6% for almost 30 years from 1970 to 2008. We examined the trends in adult OHCA survival over a 16-year period from 1998 to 2013 within a single EMS agency.Methods : Observational cohort study of adult OHCA patients treated by Tualatin Valley Fire & Rescue (TVF&R) from 1998 to 2013. This is an ALS first response fire agency that maintains an active Utstein style cardiac arrest registry and serves a population of approximately 450, 000 in 9 incorporated cities in Oregon. Primary outcomes were survival to hospital discharge in all patients and in the subgroup with witnessed ventricular fibrillation/pulseless ventricular tachycardia (VF/VT). The impact of key covariates on survival was assessed using univariate logistic regression. These included patient factors (age and sex), event factors (location of arrest, witnessed status, and first recorded cardiac arrest rhythm), and EMS system factors (response time interval, bystander CPR, and non-EMS AED shock). We used multivariate logistic regression to examine the impact of year increment on survival after multiple imputation for missing data. Sensitivity analysis was performed with complete cases.Results : During the study period, 2, 528 adult OHCA had attempted field resuscitation. The survival rate for treated cases increased from 6.7% to 18.2%, with witnessed VF/VT cases increasing from 14.3% to 31.4% from 1998 to 2013. Univariate analysis showed that younger age, male sex, public location of arrest, bystander or EMS witnessed event, initial rhythm of pulseless electrical activity (PEA) or VF/VT, bystander CPR, non-EMS AED shock, and a shorter EMS response time were independently associated with survival. After adjustment for covariates, the odds of survival increased by 9% (OR 1.09, 95%CI: 1.05–1.12) per year in all treated cases, and by 6% (OR 1.06, 95% 1.01–1.10) per year in witnessed VF/VT subgroups. Findings remained consistent on sensitivity analysis.Conclusions : Overall survival from treated OHCA has increased over the last 16 years in this community. These survival increases demonstrate that OHCA is a treatable condition that warrants further investigation and investment of resources.